A New Antirotation Strategy of K-Wire Tension Band Therapy for Patellar Fracture - Sun, Fengpo; Zhang, Yawen; Ji, Quan; Zhang, Tongyi; Zhu, Yi; Zhang, Ze; Han, Ruining; Wen, Liangyuan (Frontiers in Surgery, 2022)
Background: Patellar fracture is a common scenario in orthopaedic clinics. Many methods have been shown to be effective in the fixation of patellar fracture. However, there are few studies on the anti-rotation effect of these methods. The purpose of this study was to present a new strategy of K-wire tension band therapy for patellar fracture and explore the anti-rotation effect of modified tension band method on patellar fracture. Methods: A retrospective clinical observation study was conducted on 75 patients with patellar fracture. 46 patients were enrolled to Traditional Group who received traditional K-wire tension band method. The Modified Group included 29 patients who received our new strategy. The operation time, intraoperative blood loss and fracture healing time were collected to compare the the 2 operations, KSS scores after operation and complications were recorded and retrieved to indicate of the effectiveness of the 2 treatments. Results: The preoperative baseline data (gender, age, fracture types) of the 2 groups were no significant statistical difference. Similarly, there was no significant difference in operation time, intraoperative blood loss and fracture healing time between the 2 groups. The KSS clinical scores one year after operation was 90 (84, 95) for traditional group as compared with 99 (97, 100) in modified group (P<0.05). The KSS functional scores one year after operation in 2 groups were 90 (65, 90) and 100 (90, 100) (P<0.05). The incidences of complication due to the rotation of K-wires in the traditional group and the modified group were 76.1% (35 of 46) and 6.9% (2 of 29) with significant statistic difference (P<0.05). Conclusions: This study shows that our modified tension band therapy is an effective strategy for anti-rotation in the treatment of patellar fracture and proved to attain better clinical outcomes than traditional K-wire tension band method. This new strategy may be a safe and effective clinical technique for the treatment of patellar fracture. However, more prospective randomized controlled trial with larger sample size are still needed to confirm its efficacy.